2019
DOI: 10.18203/2320-6012.ijrms20192909
|View full text |Cite
|
Sign up to set email alerts
|

Perception of dental practitioners in and around Kanpur city towards forensic odontology: a cross sectional study

Abstract: Background: In the present era, forensic odontology has expanded as one of the most remarkable and commendable branches of Forensic Sciences. Through forensic odontology, a dentist plays a very important role in crime investigation of any type. The main objective of the present study was to evaluate the knowledge, percipience and practical perception of forensic odontology among the dental practitioners in and around Kanpur city.Methods: A cross-sectional study was conducted from Jan-Mar 2019 among 207 dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…recent study in Kanpur revealed inadequate knowledge of FO in 70% of the DPs. 11 The DPs in Varanasi city also revealed inadequate knowledge and awareness of FO. 12 Harchandani et al conducted a cross-sectional study of 300 DPs in Pune.…”
Section: Discussionmentioning
confidence: 99%
“…recent study in Kanpur revealed inadequate knowledge of FO in 70% of the DPs. 11 The DPs in Varanasi city also revealed inadequate knowledge and awareness of FO. 12 Harchandani et al conducted a cross-sectional study of 300 DPs in Pune.…”
Section: Discussionmentioning
confidence: 99%
“…Jayalakshmi Kumaraswamy et al (2018) studied knowledge, attitude, and awareness of forensic odontology among medical students where (25%) had handled forensic dentistry case in emergency medicine and only 44% of participants were aware about the significance of maintaining dental records4. Mehrotra et al (2019) concluded that 69.5% dental practitioners had knowledge about the role of dentist in FO and 79% were willing to attend the CDEs on Forensics11 . As in our study,89.1% nurses were interested to participate in workshops and seminars on forensic odontology.…”
mentioning
confidence: 99%